Fear of independence: A psychoanalytic approach to the main female character’s longing for love in Cantik Itu Luka - Hargita, Bhramastya Sandy; Nurhadi, Nurhadi; Roding, Aesoh (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2026)
One of the psychological issues often experienced by women is a fear of independence. This issue can affect women from diverse backgrounds and is reflected in the novel Cantik Itu Luka. This study aims to explain the variations, causes, and coping efforts related to women's fear of independence as depicted in the novel. The research employs a psychoanalytic approach. Data were collected through close reading and detailed note-taking. The validity of the data was ensured through semantic validity using intrarater techniques involving repeated and careful readings. The findings reveal three key variations of fear of independence experienced by the character Si Cantik: (1) yearning for a partner who can provide protection, care, and happiness, (2) a desire to always be looked after, and (3) anxiety about living alone and being abandoned by a partner. The causes of this fear are: (1) overprotective parenting that excessively interferes in a child’s life, and (2) a negative self-concept related to physical appearance. Despite these tendencies, Si Cantik eventually overcomes her fear through: (1) recognizing her inner strength and potential, and (2) learning to respect herself while accepting her weaknesses.